Disharmony of the Principle of Marital Integrity in Divorce Application Decision Number 3701/Pdt.G/2024/PA.JS. Analysis of Legal Formality and Sociological Reality - Nur Sa’adah; Amin Songgirin; Slamet Riyady (CV. RADJA PUBLIKA, 2025)
This study analyzes the disharmony between the principle of marital integrity as a legal norm and the sociological reality reflected in Divorce Petition Number 3701/Pdt.G/2024/PA.JS, particularly regarding the emergence of polyandry in the parties’ marital conflict. In Islamic family law and Indonesian positive law, the principle of marital integrity places divorce as a last resort to preserve family stability; however, judicial practice demonstrates that when the substantive objectives of marriage are no longer achieved, maintaining a formal marital relationship may instead create injustice. This research employs a normative legal method using statutory, conceptual, and case approaches, supported by qualitative analysis through legal and socio-legal interpretation of the judge’s considerations. The findings show that the judge interpreted the principle of marital integrity not textually but functionally, as an evaluative instrument to assess the sustainability of the marriage’s objectives. In this case, polyandry was viewed not only as a violation of legal norms but also as evidence of the breakdown of marital relations caused by prolonged conflict. The judge’s reasoning reflects a shift in ratio decidendi from a legalistic approach toward a socio-juridical perspective that considers psychological, social, and welfare aspects of the parties. Accordingly, the divorce decision was understood as a means of protecting individual dignity and well-being in line with the principle of legal benefit and the paradigm of maqāṣ id al-sharī‘ah. The novelty of this study lies in reconstructing the principle of marital integrity as a relational and conditional principle rather than an absolute one, thereby demonstrating that the tension between legal formality and sociological reality provides interpretative space for judges to balance legal certainty, substantive justice, and social benefit within the development of Islamic family law in Indonesia.